Spatial and temporal patterns of foraging of harbour seals (Phoca vitulina) in Porsangerfjord: from behavioural interpretation to resource selection. - Ramasco, Virginie (UiT The Arctic University of Norway, 2015)
Paper I of this thesis is not available in Munin: Ramasco V, Biuw M, & Nilssen KT: Improving time budget estimates through the behavioural interpretation of dive bouts in harbour seals. Available in Animal Behaviour, 2014, vol. 94 The coastal cod stock of the Porsangerfjord has drastically declined in the 80’s and never fully recovered since. A population of harbour seals, known to be resident in the fjord all year round, has been hypothesised to act as predator-pit for cod in the area, affecting its lack of recovery. In order to understand the role of these seals in this local marine ecosystem, their foraging behaviour was investigated by assessing the presence of preference for certain prey and the behavioural response to the seasonal dynamics of prey distribution in the fjord. The movement patterns of individual harbour seals (n = 15) were followed between 2009 and 2013. The data obtained (i.e. GPS location, time-depth dive profiles, etc.) were first thoroughly analysed to provide a robust interpretation of the behavioural patterns of activities of the single individuals and identify the methodological caveats in the detection of foraging behaviour. Among the major results, two types of resting behaviour at sea were described, in the form of prolonged periods at surface but also as resting dives, a behaviour never documented before for this species. The patterns of activity suggested that harbour seals mainly forage during daylight in autumn and spring in this area. The foraging locations identified were then compared to the availability of potential prey in the fjord (i.e. herring, capelin, small and large codfish and sculpins). The availability of prey was assumed to be dependent on their biomass densities, their distance from the seals’ haulout sites and the accessibility of the areas where prey was located. The latter could be restricted for example by the presence of sea ice in winter and spring. Results on the analyses of prey selection suggested that harbour seals in Porsangerfjord had a ...